2004
DOI: 10.1007/s10038-004-0189-5
|View full text |Cite
|
Sign up to set email alerts
|

An insertion/deletion TEX28 polymorphism and its application to analysis of red/green visual pigment gene arrays

Abstract: TEX28 gene (fTEX) is present immediately downstream of the red/green visual pigment gene array on the human X chromosome. Its pseudogene (pTEX) that lacks exon 1 is present within the array between pigment genes. We found that both fTEX and pTEX genes had a 697 bp insertion/deletion polymorphism in their introns 3. In color-normal male subjects, the frequency of the 697 bp region was 43% (40/94) in pTEX and 97% (91/94) in fTEX in the array of Red-pTEXGreen-fTEX and 10% (9/94) in pTEX and 87% (41/47) in fTEX in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Few studies on TEX28 have been published, 911 and the expression studies we performed revealed that TEX28 is expressed in blood, kidney, and testis at the mRNA level. Although the expression in testis is consistent with previous findings, Chen et al 29 did not report expression in kidney and did not test for expression in blood.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Few studies on TEX28 have been published, 911 and the expression studies we performed revealed that TEX28 is expressed in blood, kidney, and testis at the mRNA level. Although the expression in testis is consistent with previous findings, Chen et al 29 did not report expression in kidney and did not test for expression in blood.…”
Section: Discussionmentioning
confidence: 85%
“…The realtime assay targeted on the opsin genes confirmed previous predicted findings of opsin gene numbers in the Minnesota pedigree. 4 Only three copies of TEX28 have been reported within the opsin gene array, 9,11 though the real-time assay targeted on the TEX28 gene indicated that the affected male subjects had up to four copies of TEX28 in the BED and five copies in the Minnesota phenotypes in contrast to the 3 copies in the unaffected males. Two families from the United Kingdom showed either fewer (one) or greater (four) number of copies in the affected samples when compared with the unaffected samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reason, relationships observed in one population are unlikely to apply to others. For example, the 697 bp deletion in TEX28 within the opsin locus was associated with red-green color blindness in Japanese [20]. Kanjanawadee et al used this deletion as a molecular marker to study the association between color blindness and G6PD gene in Karen populations from central Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…(87) There are minimal studies on CXorf2 in the literature, and only 3 copies of CXorf2 have been reported within the opsin gene array. (156,157) Figure 3a shows quantification of opsin gene expression by real-time PCR. Expression pattern follows the number of copies previously reported by Young et al (84) Figure 3b shows quantification of CXorf2 gene expression by real-time PCR.…”
Section: Myp1 Locus On Chromosome Xq273–28mentioning
confidence: 99%